Ultrasonography B-mode, elastography (acoustic radiation force impulse), color doppler and hysteroscopy uterine in postpartum in Santa Ines sheep - Mariano, Renata Sitta Gomes [UNESP] (2018)
The aim of this study was to evaluate the uterine characteristics of Santa Inês sheep during the postpartum period, using mode B-mode ultrasonography, elastography ARFI (acoustic radiation force impulse), Doppler and hysteroscopy, with emphasis on the early diagnosis of reproductive alterations, evaluation of development and regression during this period. Twenty Santa Inês sheep were used and designated after clinical and obstetric evaluation. B-mode, Doppler and elastography ARFI evaluations were performed by transabdominal approach using the Siemens S2000 ultrasound system, with a multi-frequency and convex transducer of 5.0 to 8.0 MHz. Ultrasonography of the uterine structure was performed at immediate postpartum (M0) and sequentially every 48 hours, during 30 days, totaling 16 experimental samples. Ultrasonography characteristics of the uterus (echogenicity, echotexture, and biometry), vascular parameters (color Doppler) and stiffness aspects (qualitative and quantitative elastography) of the uterine structures were evaluated during the postpartum. Hysteroscopy evaluation of the uterine involution of the sheep was performed as follows: immediate moment after lambing (M0) and sequentially every 6 hours, until the moment where the endoscopic access to the uterus through the cervix was no longer possible. Uterine biopsy was performed at the same moments. The experimental design will be completely randomized, with a significance level of 5% for tests performed.